Expression of a Patatin-like Protein in the Anthers of Potato and Sweet Pepper Flowers. - Vancanneyt, G. (1989)
Patatin, the major glycoprotein in potato tubers, is encoded by a multigene family. RNA and protein analyses reveal that a homologous mRNA and an immunologically cross-reacting protein can be found in potato flowers, which is similar to patatin in that it displays a lipid acyl hydrolase activity. The patatin-like protein found in flowers has a higher molecular weight than the authentic tuber patatin. Deglycosylation experiments show that this is not due to differences in the glycosylation pattern. Immunocytochemical analysis shows the patatin-like protein to be present only in the epidermal cell layer of the anther, the exothecium, and in petals of potato flowers. Furthermore, the fact that a patatin-like protein can be detected in a similar tissue in sweet pepper, another solanaceous plant, could give a clue concerning the evolutionary origin of patatin.